2009
DOI: 10.1063/1.3065030
|View full text |Cite
|
Sign up to set email alerts
|

Free electron behavior in InN: On the role of dislocations and surface electron accumulation

Abstract: The free electron behavior in InN is studied on the basis of decoupled bulk and surface accumulation electron densities in InN films measured by contactless optical Hall effect. It is shown that the variation in the bulk electron density with film thickness does not follow the models of free electrons generated by dislocation-associated nitrogen vacancies. This finding, further supported by transmission electron microscopy results, indicates the existence of a different thickness-dependent doping mechanism. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 22 publications
2
40
0
Order By: Relevance
“…2 and Table I). It has been argued in the literature that either dislocations 63,64 or H and O impurities, 16,17,65 are most likely the sources of the unintentional n-type conductivity in as-grown InN. However, usually the edge type dislocations have been considered when no correlation between free electron concentration and the dislocation densities is reported.…”
Section: Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…2 and Table I). It has been argued in the literature that either dislocations 63,64 or H and O impurities, 16,17,65 are most likely the sources of the unintentional n-type conductivity in as-grown InN. However, usually the edge type dislocations have been considered when no correlation between free electron concentration and the dislocation densities is reported.…”
Section: Microstructurementioning
confidence: 99%
“…In addition, a strong electron accumulation occurs at the InN film surfaces 12,13 with a large sheet density in the low-to-mid 10 13 cm À2 range. [12][13][14][15][16][17] Consequently, detecting potential p-type conductivity in the InN bulk using conventional contact-based electrical measurements is not possible, since the surface inversion layer with high electron density conceals the region with free holes. 18 Up to date, only Mg has proven to successfully p-type dope InN, [18][19][20][21] and free holes in InN:Mg films have been experimentally identified by electrolyte capacitance-voltage, 18,22,23 thermopower, [23][24][25] 27 and infrared reflectometry 28 measurements.…”
Section: Introductionmentioning
confidence: 99%
“…SE allows access to the dielectric function (DF) of individual constituents of layered heterostructures and it is widely employed in fundamental and applied materials research. [13][14][15][16] The DF is governed by electronic transitions and provides the optical constants and information on the electronic structure of the material. SE in the near-infrared-visible-ultraviolet region was used to study EG obtained by different techniques, 17-21 expfoliated graphene, 22,23 as well as for in situ monitoring of graphene growth on metals.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] Recently, it has been shown that hydrogen is ubiquitous and can be found in significant concentrations in c-plane InN films grown by molecular beam epitaxy (MBE). 2,[5][6][7]9 However, nothing is known about the unintentional incorporation of hydrogen in InN films with surface orientations different from the conventional c-plane. This issue is particularly important in view of the generally higher free electron concentrations observed in nonpolar InN films compared to polar material.…”
Section: Introductionmentioning
confidence: 99%